Time and space in biogeography: response to Parenti & Ebach (2013). (21st June 2013) - de, Mark; Stelbrink, Björn; Page, Timothy J.; Phillips, Matthew J.; Lohman, David J.; Albrecht, Christian; Hall, Robert; von, Kristina; Ng, Peter K.L.; Shih, Hsi‐Te; Carvalho, Gary R.; von, Thomas; et al.
Abstract A recent Guest Editorial by Parenti & Ebach (2013, Journal of Biogeography, 40, 813–820) disagrees with the methods or interpretations in two of our recent papers. In addition, the authors open a debate on biogeographical concepts, and present an alternative philosophy for biogeographical research in the context of their recently described biogeographical subregion called 'Pandora'. We disagree with their approach and conclusions, and comment on several issues related to our differing conceptual approaches for biogeographical research; namely, our use of molecular phylogenetic analyses, including time estimates; and Parenti & Ebach's reliance on taxon/general area cladograms. Finally, we re‐examine their 'tests' supporting the existence of 'Pandora'.